Polarization of Rheumatoid Macrophages by TNF Targeting Through an IL-10/STAT3 Mechanism - Degboé, Yannick; Rauwel, Benjamin; Baron, Michel; Boyer, Jean-Frédéric; Ruyssen-Witrand, Adeline; Constantin, Arnaud; Davignon, Jean-Luc (Frontiers in Immunology, 2019)
Macrophages contribute to the pathogenesis of rheumatoid arthritis (RA). They can display different states of activation or “polarization”, notably the so-called inflammatory “M1” and the various alternative “M2” polarizations, characterized by distinct functions. Data regarding the effects of RA anti-cytokine biological disease-modifying anti-rheumatic drugs (bDMARDs) on macrophage polarization are scarce. We aimed to assess in vitro modulation of macrophage polarization by bDMARDs targeting pro-inflammatory cytokines in RA. We generated monocyte derived macrophages using blood samples from 20 RA patients with active RA and 30 healthy controls. We evaluated in vitro the impact on M1 inflammatory macrophages of: etanercept (ETA), adalimumab (ADA), certolizumab (CZP), tocilizumab (TCZ), and rituximab (RTX). We assessed the impact on macrophage polarization using flow cytometry and RTqPCR to study the expression of surface markers and perform functional studies of cytokine production, phagocytosis, and negative feedback control of inflammation. Among evaluated bDMARDs, anti-TNF agents modulated the polarization of inflammatory macrophages by decreasing inflammatory surface markers (CD40, CD80) and favoring alternative markers (CD16, CD163, MerTK). Anti-TNF agents also induced alternative functions in macrophages activated in inflammatory condition with (i) the inhibition of inflammatory cytokines (TNF, IL-6, IL-12), (ii) an increase in phagocytosis. These findings were mechanistically related to an increase in early IL-10 production, responsible for higher negative feedback control of inflammation involving SOCS3 and Gas6. This IL-10 effect was STAT3-dependent. Anti-TNF agents not only inhibit in vitro inflammatory functions of macrophages, but also favor resolution of inflammation through polarization towards alternative features specifically involving the IL-10/STAT3 axis.